1993
DOI: 10.1177/002221949302600203
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Development and Learning in the Pediatric Organ Transplant Recipient

Abstract: Although organ transplantation is considered a viable treatment approach for end-stage organ disease, few empirical investigations have assessed the effects of transplantation on the cognitive development and learning of pediatric organ transplant recipients. This article reviews studies evaluating neurocognitive changes following organ transplantation in pediatric end-stage renal and liver disease. Despite numerous methodological problems inherent in the investigations examined, the findings of some studies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 41 publications
2
25
0
1
Order By: Relevance
“…Infants and young children who undergo complex paediatric therapies, such as open heart surgery (1-5), extracorporeal membrane oxygenation (ECMO) (6)(7)(8)(9) and solid organ transplants (10)(11)(12)(13)(14), are at risk for adverse long-term outcomes. The risk factors associated with adverse outcomes are multifactorial.…”
Section: Le Suivi Des Enfants Qui Reçoivent Des Traitements Effractifmentioning
confidence: 99%
See 1 more Smart Citation
“…Infants and young children who undergo complex paediatric therapies, such as open heart surgery (1-5), extracorporeal membrane oxygenation (ECMO) (6)(7)(8)(9) and solid organ transplants (10)(11)(12)(13)(14), are at risk for adverse long-term outcomes. The risk factors associated with adverse outcomes are multifactorial.…”
Section: Le Suivi Des Enfants Qui Reçoivent Des Traitements Effractifmentioning
confidence: 99%
“…A number of reports (1)(2)(3)(4)(5) on outcomes of open heart surgery in small infants have been published, and there has been a plea for centres treating congenital heart disease to collect and analyze outcome data, and to make these available to families with affected children and other institutions (5). There are also some data on the outcomes of infants and children treated with ECMO (6-9) and those with solid organ transplants (10)(11)(12)(13)(14), but many unanswered questions remain, and the same plea can be made to centres providing these therapies.…”
Section: Le Suivi Des Enfants Qui Reçoivent Des Traitements Effractifmentioning
confidence: 99%
“…However, recent evidence indicates that while this may be true on a gross level, early cerebral damage frequently results in a decrease in overall intelligence and sequelae that are most apparent in areas of visuomotor and abstract reasoning skills, memory and learning, and perceptuomotor speed (Grant and Adams, 1986;Taylor, 1987). Major organ failure in particular has now been shown to be associated with significant cognitive delays and deficits, particularly where onset occurs in the first years of life (Davis et al, 1990;Hobbs and Sexson, 1993;Newburger, 1992;Stewart et al, 1991). Tarter et al (1988b) concluded that the evidence from the few studies available to that time on children with liver disease indicated that they are much more vulnerable to neurological disruption, and may suffer a more global intellectual deficit than adults.…”
Section: Cirrhosis Of the Livermentioning
confidence: 99%
“…Recent evidence from studies of children with liver disease supports the conclusion of Tarter et al (1988b) that young children may in fact suffer significant cognitive sequelae. A review by Hobbs and Sexson (1993) of studies involving organ failure in children indicates that end-stage liver disease secondary to biliary atresia has been linked with significant cognitive and motor developmental delays. Early onset of liver disease, especially where linked to growth retardation, has resulted in more generalized deficits than those found in adults, often affecting verbal intelligence as well as those specific areas affected in adults and older children (Stewart et al, 1991).…”
Section: Cirrhosis Of the Livermentioning
confidence: 99%
“…Research with these children and their families has focussed primarily on psychosocial functioning and adjustment (Shaben, 1993;Postlethwaite, Garralda, Eminson et al, 1996;Soliday, Kool and Lande, 2000;Fielding and Brownbridge, 1999;Brownbridge and Fielding, 1991;Reynolds, Garralda, Postlethwaite et al, 1991;Douglas, Hulson and Trompeter, 1998;Brownbridge and Fielding, 1989). As a result, there are relatively few existing studies addressing aspects of school functioning in this group of children (Oomen, Hulstijn-Dirkmaat, Braun et al, 2000;Lawry, Brouhard and Cunningham, 1994;Garralda, Jameson, Reynolds et al, 1988;Fukunishi and Honda, 1995;Fukunishi and Kudo, 1995;Hobbs and Sexson, 1993;Beadles, Stephenson and Watson, 1997). Moreover, the studies in question have drawn almost exclusively on quantitative data, whereas qualitative methodologies have been scarcely used.…”
Section: Introduction and Contextmentioning
confidence: 99%